PHBV/Beer spent grain fibres composites for food packaging : processability and film properties - Cunha, Mara (2013)
The high cost, small processing window and poor mechanical properties of polyhydroxyalkanoates hamper their use in demanding packaging applications such as thin films. We report here on the compounding, processability and film blowing of polyhydroxybutyrate-valerate (PHBV)/beer spent grain (BSG) fibers composites. BSG are by-products from the beer industry and were submitted to an acid/caustic treatment followed by successive grinding processes to achieve BSG fibres with mean size of the order of 20 microns. BSG fibers were compounded with a commercial PHBV (ranging from 1wt% to 20 wt%) aiming at reducing the final cost of the package and improving the low melt viscosity of PHBV, thus enhancing the processability of the resulting biocomposites. PHBV/BSG fibers compounds were produced using a twin-screw mini-extruder. Processability of the compounds was studied by adding a slit die (to shape the melt into films), a cooling bath and a haul off to the mini-extrusion line (Fig 1, C, D, E, B respectively). An optimum temperature profile was found for extruding the compound, but beyond 10 wt% BSG fibers, the melt could not be further processed as rheological data indicate that a three dimensional network builds up in the PHBV matrix. However, draw down ratios as much as 25 could be achieved. The outputs of the processability study are two formulations which were scaled up for the production of thin films (from 130 to 50 microns) using a lab-scale film blowing line (Fig. 2). Electronic microscopy reveals a poor adhesion between PHBV and BSG fibers. The mechanical, structural and barrier properties of blown films (summarized in Table 1) are discussed in light of the film processing parameters studied, namely the blown up ratio and the take up ratio.